Orienting of Attention to Gaze Direction Cues in Rhesus Macaques: Species-Specificity, and Effects of Cue Motion and Reward Predictiveness - Yu, Dian; Teichert, Tobias; Ferrera, Vincent P. (Frontiers in Psychology, 2012)
Primates live in complex social groups and rely on social cues to direct their attention. For example, primates react faster to an unpredictable stimulus after seeing a conspecific looking in the direction of that stimulus. In the current study we tested the specificity of facial cues (gaze direction) for orienting attention and their interaction with other cues that are known to guide attention. In particular, we tested whether macaque monkeys only respond to gaze cues from conspecifics or if the effect generalizes across species. We found an attentional advantage of conspecific faces over that of other human and cartoon faces. Because gaze cues are often conveyed by gesture, we also explored the effect of image motion (a simulated glance) on the orienting of attention in monkeys. We found that the simulated glance did not significantly enhance the speed of orienting for monkey face stimuli, but had a significant effect for images of human faces. Finally, because gaze cues presumably guide attention towards relevant or rewarding stimuli, we explored whether orienting of attention was modulated by reward predictiveness. When the cue predicted reward location, face and non-face cues were effective in speeding responses towards the cued location. This effect was strongest for conspecific faces. In sum, our results suggest that while conspecific gaze cues activate an intrinsic process that reflexively directs spatial attention, its effect is relatively small in comparison to other features including motion and reward predictiveness. It is possible that gaze cues are more important for decision-making and voluntary orienting than for reflexive orienting.